Predictive Risk Factors for First-Onset Lumbopelvic Pain in Postpartum Women: A Systematic Review. Issue 3 (July 2019) - Christopher, Shefali; McCullough, Jeremy; Snodgrass, Suzanne J.; Cook, Chad
Abstract : Background: Lumbopelvic pain is common during pregnancy and postpartum. This pain has been linked to a variety of comorbidities, such as depression. Although pain is common in the postpartum period, the etiology of first-onset pain is unclear and the risk factors associated with this pain in the postpartum period are unknown. Objectives: The objective of the review was to determine risk factors for first-onset lumbopelvic pain during the postpartum period. Study Design: Systematic review. Methods: Included articles were prospective cohort studies that identified modifiable and nonmodifiable risk factors for first-onset lumbopelvic postpartum pain. Articles were selected following a comprehensive search of 4 databases. The Quality in Prognostic Studies tool was used to evaluate the quality of studies. Risk factors from the articles were categorized as extrinsic, intrinsic, or mixed and ranked by the strength of their association statistic. Results: Four articles met the inclusion criteria. The pooled incidence of first-onset lumbopelvic pain was 32%. Of the 11 risk factors investigated for low back pain, cesarean delivery (CD) with epidural anesthesia, duration of first stage of labor, age of the mother, race, and urinary tract infections were significantly predictive of first-onset low back pain. Nine risk factors were investigated for pelvic pain; none were significant. Conclusion: First-onset low back pain is present among postpartum women. The 5 risk factors identified in single studies were nonmodifiable. High-quality prognostic studies need to more consistently investigate risk factors for first-onset back pain in the postpartum pain.